Efficacy and safety of the herbal formula Naesohwajung-tang for functional dyspepsia: a randomized, double-blind, placebo-controlled, multi-center trial - Ha, Na-Yeon; Ko, Seok-Jae; Park, Jae-Woo; Kim, Jinsung (Frontiers in Pharmacology, 2023)
Background: Current treatment and management options for functional dyspepsia (FD) often fail to alleviate symptoms. Naesohwajung-tang (NHT) is a herbal formula frequently used to treat FD in traditional Korean medicine. However, few animal and case reports on the use of NHT for FD treatment exist, and the clinical evidence remains deficient. Objectives: This study aimed to evaluate the efficacy of NHT in patients with FD. Methods: We enrolled 116 patients with FD at two study sites in this 4 week, randomized, double-blind, placebo-controlled trial and randomly assigned them to either the NHT or placebo group. To evaluate the efficacy of NHT, the primary endpoint was a score on the total dyspepsia symptom (TDS) scale after treatment. The overall treatment effect (OTE), single dyspepsia symptom (SDS) scale, food retention questionnaire (FRQ), Damum questionnaire (DQ), FD-related quality of life (FD-QoL) questionnaire, and gastric myoelectrical activity measured using electrogastrography were evaluated as secondary outcomes. Laboratory tests were performed to confirm the safety of the intervention. Results: The 4 week administration of NHT granules demonstrated a significantly higher reduction in the TDS (P < 0.05) and a higher degree of improvement in the TDS (P < 0.01) than the placebo group. Patients who underwent NHT had a significantly higher OTE and a greater increase in the degree of improvement in scores such as epigastric burning, postprandial fullness, early satiation, FD-QoL, and DQ (P < 0.05). Additionally, the NHT group showed a greater effect in preventing a decrease in the percentage of normal gastric slow waves after meals than the placebo group. As a result of subgroup analyses using the degree of improvement in TDS, NHT was found to be more effective than placebo in female, younger patients (< 65 years), with a high body-mass index (≥ 22), overlap type, food retention type, and Dampness and heat in the spleen and stomach systems pattern. There was no significant difference in the incidence of adverse events between the two groups. Conclusions: This is the first randomized clinical trial to verify that NHT leads on symptom relief in patients with FD. Clinical Trial Registration: https://cris.nih.go.kr/cris/search/detailSearch.do/17613; identifier: KCT0003405.